APPLICATION OF HABITUATION METHODS TO ISLAMIC RELIGIOUS LEARNING IN DEVELOPING RELIGIOUS AND MORAL VALUES IN EARLY CHILDREN - Normilah, Normilah; MY, Mahmud; Musli, Musli (JARITA : Journal of Children’s Education and Learning Research, 2023)
The habituation method is an activity that is carried out continuously so that it becomes a habit. The purpose of this study was to find out how the efforts of teachers in developing religious and moral values ​​of early childhood through the application of the habituation method. This research method uses a descriptive qualitative approach. Data collection is done by observation, interviews and documentation. Data analysis used data reduction, data presentation, data verification and trust test using data triangulation. The results of the study show that the teacher's efforts in developing the development of religious and moral values ​​in children through the habituation method are as follows: routinely guiding prayer activities before and after carrying out daily activities, Duha prayer, polite speech to familiarize noble behavior, exemplary, maintain personal and environmental hygiene, and programmatically memorize short letters and daily prayers. the conclusion that these activities are a form of habituation can be applied to early childhood in developing religious and moral values.